Islamic banks vs conventional banks in Indonesia: an analysis on financial performances - Sukmana, Raditya; Febriyati, Nur Ahlina (Penerbit Universiti Kebangsaan Malaysia, 2016)
Islamic banks in Indonesia havebeen in existence for more than two decades. Substantial development has taken place in this largest Muslim country. Regulator, academicians, and practitioners have been providing significant support with the objective of improving the performance of the Islamic banking. Hence, it is timely to assess whether its performance differs than that of the conventional banks. This paper aims to describe and critically evaluate and compare the financial performance of Islamic banks to that of conventional banks. Data of Capital Adequacy Ratio (CAR), Return on Asset (ROA), Operational Cost/ Operational Revenue (BOPO), Non-Performing Loan (NPL) /Non Performing Financing (NPF) and Loan Deposit Ratio (LDR)/ Financing Deposit Ratio (FDR) for Islamic and conventional banks are examined. The analysis of monthly data covers the period from January 2004 to July 2014 (127 observations). Paired sampled t-test was adopted to see whether there are significant differences in the financial ratios between both banks. This study found that CAR, ROA, BOPO and NPL of conventional banks are significantly higher than that of Islamic banks but not FDR. Based on the result of capital adequacy, the findings suggest that Islamic banks need to have more capital to face the involved risk as that of conventional banks. Conventional banks need to function them selves as financial intermediaries to support the real sector as that of Islamic banks.